Development of running is not related to time since onset of independent walking, a longitudinal case study - Margit M. Bach; Coen S. Zandvoort; Germana Cappellini; Germana Cappellini; Yury Ivanenko; Francesco Lacquaniti; Francesco Lacquaniti; Andreas Daffertshofer; Nadia Dominici (Frontiers in Human Neuroscience, 2023)
IntroductionChildren start to run after they master walking. How running develops, however, is largely unknown.MethodsWe assessed the maturity of running pattern in two very young, typically developing children in a longitudinal design spanning about three years. Leg and trunk 3D kinematics and electromyography collected in six recording sessions, with more than a hundred strides each, entered our analysis. We recorded walking during the first session (the session of the first independent steps of the two toddlers at the age of 11.9 and 10.6 months) and fast walking or running for the subsequent sessions. More than 100 kinematic and neuromuscular parameters were determined for each session and stride. The equivalent data of five young adults served to define mature running. After dimensionality reduction using principal component analysis, hierarchical cluster analysis based on the average pairwise correlation distance to the adult running cluster served as a measure for maturity of the running pattern.ResultsBoth children developed running. Yet, in one of them the running pattern did not reach maturity whereas in the other it did. As expected, mature running appeared in later sessions (>13 months after the onset of independent walking). Interestingly, mature running alternated with episodes of immature running within sessions. Our clustering approach separated them.DiscussionAn additional analysis of the accompanying muscle synergies revealed that the participant who did not reach mature running had more differences in muscle contraction when compared to adults than the other. One may speculate that this difference in muscle activity may have caused the difference in running pattern.